The role of the European Union's neighbourhood policy in developing cross-border cooperation in the Polish-Ukrainian borderland - Tomasz Studzieniecki; Monika Szyda; Katarzyna Szelągowska-Rudzka (Central European Economic Journal (CEEJ), 2024)
Cross-border cooperation, financially supported by the EU Neighbourhood Policy instruments, is an important factor for the socio-economic development of cross-border areas at the EU's external borders. This paper is devoted to cross-border cooperation on the Polish-Ukrainian border, which was financed by the Cross-Border Cooperation Program Poland-Belarus-Ukraine 2014-2020, which was one of the programs of the European Neighbourhood Policy. This issue becomes particularly significant in the context of cooperation with Ukraine, which is challenging due to the ongoing conflict in its territory. There is a need to examine existing solutions and propose future directions for cross-border cooperation. The aim of the article was to present evolution and identify the attributes of the European Neighbourhood Policy, which is a key instrument of the development of cross-border cooperation at the EU's external borders. The second aim was a multidimensional analysis of Polish-Ukrainian cooperation during a period 2014-2020, taking into account the structure of projects, partners and areas of cooperation. The structure of partners was examined and discussed based on their status, sector, and level of activity. The research augmented the current knowledge in the field of cross-border collaboration supported by the European Neighbourhood Policy. The management of crossborder cooperation on the Polish-Ukrainian border can benefit from the study's practical conclusions.
Keywords: R58; E61; F59; 330; Cross-border cooperation; Ukraine; European Neighbourhood Policy; projects; development